Composición y diversidad del matorral desértico rosetófilo en dos tipos de suelo en el noreste de México - Alanís-Rodríguez, Eduardo; Mora-Olivo, Arturo; Jiménez-Pérez, Javier; González-Tagle, Marco Aurelio; Yerena Yamallel, José Israel; Martínez-Ávalos, José Guadalupe; González-Rodríguez, Laura Elena (Instituto de Ecología, A.C., 2015)
The floristic and ecological characteristics of a rosette desert scrub in two areas differing in soil type (Rendzina + Lithosol, medium texture, lithic, and Regosol calcareous + Lithosol, medium texture) in northeastern Mexico were studied. Using 44 plots of 20 × 10 m we sampled succulents, shrubs and tree species. We estimated the following vegetation variables: density (N/ha), crown cover (m2/ha), frequency, importance value index (IVI), in addition to α- and β-diversity. By ANOVA, no significant differences were found in richness, diversity and crown cover. The results indicate that the floristic composition was different between the two soil types, the density being significantly higher in the Regosol (8909 N/ha) than in the Rendzina (4790 N/ha). The predominance of cacti is favored by low moisture retention in the calcaric + Litosol Regosol association.